Intermediate Greek grammar: syntax for students of the New Testament - Mathewson, David (Baker Academic, a division of Baker Publishing Group, 2016)
"This intermediate grammar for students of New Testament Greek incorporates the advances of recent linguistic research in an accessible and understandable way."--